Sex linked behavioral and hippocampal transcriptomic changes in mice with cell-type specific Egr1 loss - Swilley, Cody; Lin, Yu; Zheng, Yuze; Xu, Xiguang; Liu, Min; Jarome, Timothy; Hodes, Georgia E.; Xie, Hehuang (Frontiers in Neuroscience, 2023)
The transcription factor EGR1 is instrumental in numerous neurological processes, encompassing learning and memory as well as the reaction to stress. Egr1 complete knockout mice demonstrate decreased depressive or anxiety-like behavior and impaired performance in spatial learning and memory. Nevertheless, the specific functions of Egr1 in distinct cell types have been largely underexplored. In this study, we cataloged the behavioral and transcriptomic character of Nestin-Cre mediated Egr1 conditional knockout (Egr1cKO) mice together with their controls.Although the conditional knockout did not change nociceptive or anxiety responses, it triggered changes in female exploratory activity during anxiety testing. Hippocampus-dependent spatial learning in the object location task was unaffected, but female Egr1cKO mice did exhibit poorer retention during testing on a contextual fear conditioning task compared to males. RNA-seq data analyses revealed that the presence of the floxed Egr1 cassette or Nestin-Cre driver alone exerts a subtle influence on hippocampal gene expression. The sex-related differences were amplified in Nestin-Cre mediated Egr1 conditional knockout mice and female mice are more sensitive to the loss of Egr1 gene. Differentially expressed genes resulted from the loss of Egr1 in neuronal cell lineage were significantly associated with the regulation of Wnt signaling pathway, extracellular matrix, and axon guidance. Altogether, our results demonstrate that Nestin-Cre and the loss of Egr1 in neuronal cell lineage have distinct impacts on hippocampal gene expression in a sexspecific manner.